18n-16(-n-15)=12(n+9)

Simple and best practice solution for 18n-16(-n-15)=12(n+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18n-16(-n-15)=12(n+9) equation:


Simplifying
18n + -16(-1n + -15) = 12(n + 9)

Reorder the terms:
18n + -16(-15 + -1n) = 12(n + 9)
18n + (-15 * -16 + -1n * -16) = 12(n + 9)
18n + (240 + 16n) = 12(n + 9)

Reorder the terms:
240 + 18n + 16n = 12(n + 9)

Combine like terms: 18n + 16n = 34n
240 + 34n = 12(n + 9)

Reorder the terms:
240 + 34n = 12(9 + n)
240 + 34n = (9 * 12 + n * 12)
240 + 34n = (108 + 12n)

Solving
240 + 34n = 108 + 12n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-12n' to each side of the equation.
240 + 34n + -12n = 108 + 12n + -12n

Combine like terms: 34n + -12n = 22n
240 + 22n = 108 + 12n + -12n

Combine like terms: 12n + -12n = 0
240 + 22n = 108 + 0
240 + 22n = 108

Add '-240' to each side of the equation.
240 + -240 + 22n = 108 + -240

Combine like terms: 240 + -240 = 0
0 + 22n = 108 + -240
22n = 108 + -240

Combine like terms: 108 + -240 = -132
22n = -132

Divide each side by '22'.
n = -6

Simplifying
n = -6

See similar equations:

| (8/5)x=273 | | 22+-k=20 | | 7-8n+48=-97 | | 2(1)-3y=5 | | 5+(x+3)+5+2(x+3)=y | | x+5=2x+22 | | 5=-12 | | 6x+4+5x=81 | | 5=-20 | | x(2x+3)(9)=810 | | 3+f=9 | | 2x+3.25(50)=275 | | 2x-3(0)=5 | | 4n-2(n+2)=2(7n-2) | | 2a-5=27 | | 5x-2(x-5)=-8+5x+14 | | (8/5)+x=273 | | 27=2a-5 | | 4-3x=16+1x | | -3(t-3)+5t=8t-6 | | f+5f=50 | | 2(0)-3y=5 | | 12-4x=9+x | | -5=4+8x-1+3x | | 2x-4(x-5)=-2+3x-3 | | -3(2-r)=4r | | 4-3x=16+1 | | z=121x-241713 | | 12x^2-73x+6=0 | | 7-8(n+6)=-97 | | -4(r+6)+8=-22-6r | | 190=8-7(-3p-8) |

Equations solver categories